Tinjauan Hukum Islam Terhadap Praktek Jual Beli Singkong Dengan Sistem Tebas (Studi Kasus di Desa Terbanggi Ilir, Kecamatan Bandar Mataram, Kabupaten Lampung Tengah ) - , Surendi, Dr. M. Muhtarom, SH. MH (2016)
God created man with a nature interdependent which each other. For that God gives inspiration (ilham) to them to organize exchanges of trade and all that helpful presumably by way of sale and all means of transportation. However, there are still some practice of buying and selling going on in society is not in accordance with Islamic law. As the observation that researchers do in the village Terbanggi Ilir, Bandar Mataram subdistrict, Lampung Tengah district. are deals with practice of buying and selling cassava with a slash in terms of Islamic law. The type of research is that the researchers use, including field research, and the analytical technique used is descriptive qualitative. The steps used in taking data that is by observation and interview techniques. Based on the methods used in this study. So, if in view of Islamic law, selling cassava with slash and should not be done, because it contains of elements that are prohibited in Islam as gharar (vagueness) and gambling (speculative) there is many vagueness in quality and quantity because there is no dosage and weighing process before. Therefore, it will be better to avoid this buy and sell to the right process.